2019
DOI: 10.5977/jkasne.2019.25.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Blood Donation Intentions of Nursing College Students

Abstract: The purpose of this study was to investigate the factors influencing intentions regarding blood donation among nursing university students. Methods: We collected data from 165 nursing students at a university in D city via a self-administered questionnaire from May 28 to May 30, 2018. Results: Intentions of blood donation had significant positive correlations with blood donation motivation (r=.52, p<.001). Also, blood donation motivation had significant positive correlations with self-identity (r=.27, p=.013).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A study on blood donation knowledge in the past showed that the blood donation knowledge of participants (rate of correct answers) was 46.8% ( 41 ). Meanwhile, more recently, according to ( 42 ), the rate increased to 76.4%. However, the current study showed a decrease to 66.4%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on blood donation knowledge in the past showed that the blood donation knowledge of participants (rate of correct answers) was 46.8% ( 41 ). Meanwhile, more recently, according to ( 42 ), the rate increased to 76.4%. However, the current study showed a decrease to 66.4%.…”
Section: Discussionmentioning
confidence: 99%
“…The current knowledge of blood donation of South Koreans differed as compared to the past when it was a developing country. A study on blood donation knowledge in the past showed that the blood donation knowledge of participants (rate of correct answers) was 46 according to (42), the rate increased to 76.4%. However, the current study showed a decrease to 66.4%.…”
Section: Discussionmentioning
confidence: 99%